IMPLEMENTASI UU PERLINDUNGAN DATA PRIBADI TERHADAP KEAMANAN INFORMASI IDENTITAS DI INDONESIA - Mahameru, Danil Erlangga; Nurhalizah, Aisyah; Badjeber, Haikal; Wildan, Ahmad; Rahmadia, Haikal (Esensi Hukum, 2023)
The growth of information and communication technologies. The main obstacle that arises safeguards personal information and privacy amidst technological sophistication. The biggest challenge is developing an effective regulatory framework to protect individual privacy while facilitating technological innovation. Both the public and private sectors must exhibit significant endeavors to overcome this problem. Examining all laws and regulations pertaining to Personal Data Protection, this study employs a legislative approach, namely through the 1945 Constitution, Personal Data Protection Regulation No. 20 of 2016, Law No. 11 of 2008 Concerning Electronic Information and Transactions, and Law No. 27 of 2022 Asserting the Authority of the Minister of Communication and Information. Implementation of the Personal Data Protection Law is an important step to orderly implement regulations and prevent legal uncertainty. Delays in issuing implementing regulations can create legal uncertainty and obstruct the fulfillment of the Law's goals.